Influence of Different Side-groups and Cross-links on Phosphoric Acid Doped Radel-based Polysulfone Membranes for High Temperature Polymer Electrolyte Fuel Cells. (10th January 2017) - Singh, Bhupendra; Duong, Ngoc My Hanh; Henkensmeier, Dirk; Jang, Jong Hyun; Kim, Hyoung Juhn; Han, Jonghee; Nam, Suk Woo
Graphical abstract: Abstract: In previous work we tested the potential of Radel based membranes for use in the high temperature polymer electrolyte fuel cell (HT PEMFC), using aminoyridine (AP) and imidazole (IM) as phosphoric acid (PA) binding and crosslinking group, respectively. In this work we developed the system further by comparing AP with hydroxypyridine (HP) and IM with oxydianiline (OX). The use of OX leads to reduced PA uptake, probably due to higher reactivity, increasing the density of crosslinks. HP leads to an increased PA uptake, clearly above 300 wt% for HP-IM membranes. Conductivity correlates well with the PA uptake, and HP-IM membranes showed the highest ion conductivity, 18 mS/cm 2 at 120 °C and fully anhydrous conditions. The logarithmic value of the Young modulus, plotted against the PA uptake, shows a linear behavior, independent of the functional groups. In comparison to previous work, the slope is smaller, demonstrating that it is possible to shift the trade-off relation into a more beneficial range. In the fuel cell test, HP-IM membranes showed the best performance. Based on the peak power density, the HP-IM based system (294 mW/cm 2 at 800 mA/cm 2 ) showed a 2.5 times higher performance than the previously reported AP-IM based system.